Integration of Transformative Leadership, Artificial Intelligence, and the TPACK Framework for Efficient Pedagogy: A Documentary Analysis - Alshamsi, Aysha (International Journal of Learning, Teaching and Educational Research, 2025)
The poor academic performance of students is a challenge facing the educational systems of several countries, including the United Arab Emirates (UAE). Recent theoretical and technological advances address this challenge. This study developed an integrated leadership framework to guide K–12 school leaders by synthesizing the theories of technological pedagogical content knowledge (TPACK) and transformative leadership with artificial intelligence (AI). A qualitative documentary analysis of authoritative academic literature and national policies was conducted, applying reflexive thematic analysis to extract actionable insights. Three overarching themes emerged: (1) the impact of AI on educational leadership, highlighting AI-enabled data-driven decision-making and personalized learning as catalysts for equity and efficiency; (2) transformational leadership strategies, underscoring the need for vision setting, change management, and teacher empowerment practices; and (3) the role of the TPACK framework in ensuring pedagogically coherent and content-aligned technology adoption. Therefore, a novel TPACK–transformational leadership model that integrates learning organization principles, pedagogical leadership, and transformational change processes is proposed to drive AI integration in schools. This model enhances teaching practices and improves student outcomes. Implications for school leaders include establishing ethical governance structures, ensuring equitable access to AI tools, embedding TPACK-centered professional development initiatives, and managing the digital divide and teacher readiness challenges. A practical roadmap is offered for leaders to responsibly and sustainably harness the potential of AI in rapidly evolving educational landscapes. Although the analysis concerns the educational system in the UAE, the implications apply to other countries. https://doi.org/10.26803/ijlter.24.9.47